MENINGKATKAN PEMAHAMAN BERBAHASA MELALUI PROGRAM LITERASI DI SEKOLAH DASAR - Desi Agustini (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This journal explained how to improve language comprehension through literacy education at SD Negeri 9 Pulau Rimau school or often called the School Literacy Movement (GLS). The School Literacy Program is designed using the Read-Summarize-Tell-Share method. The subjects of this study were all students including low class (1, 2 and 3) and high class (grades 4, 5 and 6), educators (teachers), education staff, principals, and librarians. This research is carried out in accordance with the stages of development of students based on their characteristics; 1) implemented in a balanced manner; 2) use a variety of texts and pay attention to student needs; takes place in an integrated and holistic manner in all curriculum areas; 3) carried out continuously; 4) involves oral communication skills; 5) consider the diversity and conditions of the school. The results of this study students to understand the language properly and correctly.